2021
DOI: 10.1002/app.50879
|View full text |Cite
|
Sign up to set email alerts
|

Upgrading poly(styrene‐co‐divinylbenzene) beads: Incorporation of organomodified metal‐free semiconductor graphitic carbon nitride through suspension photopolymerization to generate photoactive resins

Abstract: The inclusion of the metal free semiconductor graphitic carbon nitride (g‐CN) into polymer systems brings a variety of new options, for instance as a heterogeneous photoredox polymer initiator. In this context, we present here the decoration of the inner surface of poly(styrene‐co‐divinylbenzene) beads with organomodified g‐CN via one pot suspension photopolymerization. The resulting beads are varied by changing reaction parameters, such as, crosslinking ratio, presence of porogens, and mechanical agitation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 63 publications
(67 reference statements)
2
7
0
Order By: Relevance
“…As CMp-vTA particles reside on surface with no porosity, significant photoactivity is not observed as it takes place on porous interfaces in g-CN hybrids. 31 As expected, our studies on photocatalytic RhB degradation via TT@CMp-vTA beads showed no remarkable activity on RhB degradation (Figure S3), which underlines the restricted photoactivity of TT@CMp-vTA beads. This obervation is in good agreement of a general knowledge that porosity is needed for (photo)catalysis on hybrid structures where the photoactive material should be at the inner porous interface and not on the surface.…”
Section: Nanoscale Advances Accepted Manuscriptsupporting
confidence: 70%
See 1 more Smart Citation
“…As CMp-vTA particles reside on surface with no porosity, significant photoactivity is not observed as it takes place on porous interfaces in g-CN hybrids. 31 As expected, our studies on photocatalytic RhB degradation via TT@CMp-vTA beads showed no remarkable activity on RhB degradation (Figure S3), which underlines the restricted photoactivity of TT@CMp-vTA beads. This obervation is in good agreement of a general knowledge that porosity is needed for (photo)catalysis on hybrid structures where the photoactive material should be at the inner porous interface and not on the surface.…”
Section: Nanoscale Advances Accepted Manuscriptsupporting
confidence: 70%
“…As CMp-vTA particles reside on the surface with no porosity, significant photoactivity is not observed as it takes place on porous interfaces in g-CN hybrids. 31 As expected, our studies on photocatalytic RhB degradation via TT@CMp-vTA beads showed no remarkable activity on RhB degradation (Fig. S3 † ), which underlines the restricted photoactivity of TT@CMp-vTA beads.…”
supporting
confidence: 71%
“…(a) Digital images and corresponding SEM images of reference beads (top) and beads containing photoactive groups (below) [adapted with permission from ref , copyright 2017, American Chemical Society, Washington, DC]. (b) Digital images of g-CN based PS-DVB beads under normal and UV light, and an exemplary SEM image of a bead showing a porous network [obtained from ref , published under CC-BY, copyright 2021, John Wiley and Sons].…”
Section: Resinsmentioning
confidence: 99%
“…Alternatively, semiconductors can be integrated into resins during heterophase polymerization stage via dispersing semiconductors in organic monomer phase. For example, metal-free semiconductor (graphitic carbon nitride, g-CN, post-modified to bring organodispersibility) was dispersed in organic phase and its photoactivity was harvested by conducting suspension photopolymerization (Figure b) . In this case, polystyrene-divinylbenzene (PS-DVB) beads were upgraded into a photoactive covalent porous hybrid resin where g-CN particles reside at the interface, which endows photoactivity confirmed via RhB dye photodegradation experiments.…”
Section: Resinsmentioning
confidence: 99%
“…This section is dominated by the utilization of small organic molecules that undergo photolysis to yield stable radicals. [18,19] So-formed radicals are then employed for radical polymerization of vinyl-containing monomers. [20] Nevertheless, the influence of photoredox chemistry is expanding in polymer science to access more advanced mechanisms.…”
Section: Introductionmentioning
confidence: 99%